Identification of the Mind Bomb1 Interaction Domain in Zebrafish DeltaD. - Gregory Palardy; Ajay B Chitnis (PLoS ONE)
Ubiquitylation promotes endocytosis of the Notch ligands like Delta and Serrate and is essential for them to effectively activate Notch in a neighboring cell. The RING E3 ligase Mind bomb1 (Mib1) ubiquitylates DeltaD to facilitate Notch signaling in zebrafish. We have identified a domain in the intracellular part of the zebrafish Notch ligand DeltaD that is essential for effective interactions with Mib1. We show that elimination of the Mind bomb1 Interaction Domain (MID) or mutation of specific conserved motifs in this domain prevents effective Mib1-mediated ubiquitylation and internalization of DeltaD. Lateral inhibition mediated by Notch signaling regulates early neurogenesis in zebrafish. In this context, Notch activation suppresses neurogenesis, while loss of Notch-mediated lateral inhibition results in a neurogenic phenotype, where too many cells are allowed to become neurons. While Mib1-mediated endocytosis of DeltaD is essential for effective activation of Notch in a neighboring cell (in trans) it is not required for DeltaD to inhibit function of Notch receptors in the same cell (in cis). As a result, forms of DeltaD that have the MID can activate Notch in trans and suppress early neurogenesis when mRNA encoding it is ectopically expressed in zebrafish embryos. On the other hand, when the MID is eliminated/mutated in DeltaD, its ability to activate Notch in trans fails but ability to inhibit in cis is retained. As a result, ectopic expression of DeltaD lacking an effective MID results in a failure of Notch-mediated lateral inhibition and a neurogenic phenotype.